Penguatan Islam Moderat di Madrasah Ibtidaiyah Ma’arif Singosaren Ponorogo - Nurrohman, Wawan Marsudi; Alvarozi, Matsna Zakia (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2023)
This study aims to find out things that can strengthen Moderate Islam. Through an approach at school, which is influenced by many factors, including teachers, peers, learning and parents of students. Therefore, strengthening moderate Islam is very important to support and encourage the formation of moderate student character where there is inculcation in students including faith values, worship values, and moral values. This research uses a descriptive qualitative research type. The choice of this method was carried out because the analysis could not be in the form of numbers and the researcher described more clearly all the phenomena that existed in society. This research was carried out in stages according to a predetermined schedule to obtain complete and relevant data. Data obtained from interviews and observations were presented in the form of descriptions, and processed using words that are easier to understand and understand. The results of this study say that to realize moderate Islam, habituation and activities can be carried out by students so as to foster the meaning of moderate itself. Namely the balance between belief and tolerance, as having certain beliefs but still having a balanced tolerance for other beliefs.